Avaliação cardiológica de cachorros-do-mato (Cerdocyon thous, linnaeus 1758) de cativeiro sob contenção farmacológica - Arruda, Ana Flávia Delben Pereira de (2018)
Knowledge regarding cardiac physiology and morphology in wild canids is limited, and this information is important in pathophysiological and conservational studies from these species. The aim of this study was to obtain values for cardiology parameters of the crab-eating fox kept in captivity. This study was done with 11 Cerdocyon thous raised in captivity under pharmacological containment of intramuscular 0,05 mg/kg acepromazine with 3mg/kg meperidine followed by intravenous 3 to 5mg/kg propofol. The examinations were performed by doppler echocardiography, electrocardiogram, blood pressure measurement using the doppler and oscillometric method, and chest X-ray analysis with calculus of the vertebral heart size (VHS). In general, electrocardiographic and doppler echocardiographic values are closer to domestic dogs. However, the left ventricle internal diameter in diastole was lower and the Ejection Fraction was closer to that from maned wolf (Chrysocyon brachyurus) in doppler echocardiographic test. Blood pressure values were in agreement with the literature for anesthetized domestic dogs. The subjective analysis of the thorax also resembles more to the maned wolf, with exception of the changes that we believe to be due to the nutrition. The VHS measure presented values closer to the maned wolf, despite being within the reference for domestic dogs. The cardiology parameters found in this study can be used as specific guide values for this species in the evaluation of cardiac function, as well as in other to additional studies in wild canids cardiology.